A presença do governo japonês e sua política para a preservação de memória, da identidade e perpetuação da etnia japonesa no exterior: Brasil, século XX - Gaudioso, Tomoko Kimura (2019)
As Japan reopens its ports to the outside world in 1603, there wasn’t yet among Japanese people the notion of a unified nation. Thus, Japan had to reshape its structure as a nation state and government. In this context, the land of the rising sun shows up for the first time in world history as a unified nation, having its own flag and national anthem, following the example of western countries. The Meiji Constitution is elaborated and promulgated as the first Magna Carta of modern Japan. In regards to national identity, by studying the west’s governance systems, economy, culture and technology, policymakers realized the need to bring forth a national identity, to modernize the country as well as to expand its territory. In effect, after the rise to the throne of the Meiji Emperor, Japan dominated Asia and the Pacific, with the colonization of the Pacific Islands, the invasion of Taiwan (1874) and the annexing of the kingdom of Okinawa in 1872, as was the colonial practice in the west. With Hokkaido being part of Japanese territory, there were efforts in braving it and occupying it with settlements of soldiers and their families. In 1894-1895 breaks out the sino-japanese war, followed by the russo-japanese war, in 1904-1905, with Japan emerging victorious. In 1910, Korea is annexed as a Japanese colony. The national symbols, such as the national anthem and flag are presented to the people. The figure of the emperor was presented as the absolute sovereign and representative of the Japanese people. This mythical image of the emperor persists until the end of world war two, when, through sacred imperial announcement, he declares himself as common folk, alongside its unconditional rendition to the Allies to save his people. In this context, this proposal has the intent of investigating the representativeness of the figure of the emperor of Japan since the Meiji Restoration, as representative of the Japanese people, both nationals or people of Japanese origin. Moreover, in the context of Japan’s policies of expansion beyond its national territory, investigate if this motion carried on even after the end of world war two and, it being the case, what strategy did Japan adopt regarding the rest of the world. Having this policy being adopted, identify how the collective memory of the Japanese people is preserved, considering that these people are settled in geopolitical territories external to Japan. For data collection, besides documental and bibliographic research, field research was held, most importantly, the observation of behavior pertaining the culture characteristic to the Japanese, with means to demonstrate that, in a world in which migration is more frequent and where the process of regional integration happens in a continuous way, it is possible for people to maintain their cultural identity and memory while claiming their own ethnicity, and having the State as a leading figure.